Both electrolytic and excitotoxic lesions of nucleus accumbens disrupt latent inhibition of learning in rats. - Tai, C; Cassaday, H; Feldon, J; Rawlins, J (1995)
Evidence indicating a role for the nucleus accumbens in the development of latent inhibition of learning has accumulated. Two experiments were conducted using Wistar rats to investigate this role directly. Experiment 1 used a conditioned emotional response paradigm to assess the effects of discrete electrolytic lesions in the shell region of the nucleus accumbens. Latent inhibition was attenuated by this lesion. In order to determine the contribution made by damage to fibers en passage associated with electrolytic lesions, Experiment 2 assessed the effects of NMDA-induced lesions in the shell of the nucleus accumbens in the same task. Latent inhibition was again significantly attenuated. These findings support the proposition that an intact nucleus accumbens is necessary for the normal development of latent inhibition.